Agro-Climatic Suitability Delimitation for Table and Wine Grape Crops under Irrigation Conditions in Northeastern Brazil - Teixeira, A. H. de C. (2014)
Long term weather data were used together with specific regression models involving crop coefficient (K-c), reference evapotranspiration (ET0), accumulated degree days (DDac) and precipitation (P), to develop a vineyard water indicator (VWI) for seedless table and wine grapes under different pruning periods in the Brazilian Northeast. The VWI thermo-hydrological indicator was applied together with average values of air temperature (T) for a growing season (GS) to classify the vineyard agro-climatic suitability. For table grapes, the seedless cv. 'Sugraone' used as a reference, it was observed that the region has no thermal limitation for commercial grape production. However, higher sugar contents in berries and yield would be obtained in the areas and pruning periods with higher T-GS. In relation to wine grape, cv. 'Syrah' taking as a reference, it was shown that there are some thermal limitations for the tropical wine quality. This is depending on pruning dates, lower acidity and higher potential alcohol and pH. In wines analyzed under conditions of larger TGS values, wines became unbalanced in terms of phenolic and aromatic composition. Considering the whole Brazilian Northeast region, for table grapes the best pruning periods is from July to September, while for wine grapes they are between April and June. The spatially presented analyses can subsidize vineyard water allocation criterions, when aiming at improvements of grape and wine water productivity in conditions of climate and land use changes.